Peroxisomes as emerging clinical targets in neuroinflammatory diseases - Roczkowsky, Andrej; Rachubinski, Richard A.; Hobman, Tom C.; Power, Christopher (Frontiers in Molecular Neuroscience, 2025)
Peroxisomes are membrane-bounded organelles that contribute to a range of physiological functions in eukaryotic cells. In the central nervous system (CNS), peroxisomes are implicated in several vital homeostatic functions including, but not limited to, reactive oxygen species signaling and homeostasis; generation of critical myelin sheath components (including ether phospholipids); biosynthesis of neuroprotective docosahexaenoic acid; breakdown of neurotoxic metabolites (such as very-long chain fatty acids); and, intriguingly, glial activation and response to inflammatory stimuli. Indeed, peroxisomes play a critical role in modulating inflammatory responses and are key regulators of the mitochondrial antiviral signaling (MAVS) protein-mediated response to infections. The importance of peroxisomes in CNS physiology is exemplified by the peroxisome biogenesis disorders (PBDs), a spectrum of inherited disorders of peroxisome assembly and/or abundance, that are characterized in part by neurological manifestations ranging from severe cerebral malformations to vision and hearing loss, depending on the individual disorder. Recently, peroxisome dysfunction has been implicated in neurological diseases associated with neuroinflammation including Alzheimer’s disease, amyotrophic lateral sclerosis, multiple sclerosis, and Parkinson’s disease while also contributing to the pathogenesis of neurotropic viruses including SARS-CoV-2, Human Pegivirus, HIV-1 and Zika virus. In the present review, we examine the diverse roles that peroxisomes serve in CNS health before reviewing more recent studies investigating peroxisome dysfunction in inflammatory brain disorders and also highlight potential peroxisomal targets for diagnostic biomarkers and therapeutic interventions.